Formation of consumer properties of jeweller alloys on the basis of 585 fineness gold with modifying components - Артюх, Тетяна Миколаївна; Григоренко, Інна Василівна (Technology audit and production reserves, 2015)
The research results of physical and mechanical and physical and chemical properties of gold alloys are given. An influence of the chemical composition and structure on the main indicators of quality of finished jewelry is defined. The main aim of the research was to study the patterns of properties of complex action of ligatures for the metal modifiers (silicon, cobalt, zirconium, manganese, boron). The influence of the main alloying components and modifying additives in the "gold-silver-copper" system on the formation of physical and mechanical properties of jewelry, reliance of alloy structure formation process from heat treatment regime is proved. The efficiency of improvement of key indicators of jewelry consumer properties by optimizing the main alloying components and modifying additives of B, Co, Zr, Mn, Si in jewelry alloys from 585 fineness gold is shown. The results related to metallurgy of precious metals and can be used in the jewelry industry.